Antibacterial test of Rhizophora apiculata extract originated from Mangrove Wonorejo Surabaya against Staphylococcus aureus and Escherichia coli - Widiani, Diana Yunita; Aliyah, Salsabila Diva; Awwalia, Era Fitri; Al-Husen, Ibrahim Muhammad; Komarudin, Paroso (Journal of Marine Resources and Coastal Management, 2023)
Rhizopora apiculata is a type of mangrove that has the potential as a source of antibacterial. This plant is used as medicine by coastal communities in Indonesia because it contains useful active ingredients. This research aims to study Rhizophora apiculata antibacterial potential against pathogenic bacteria Staphylococcus aureus and Escherichia coli. The samples used were Rhizophora apiculata leaves from Mangrove Wonorejo Surabaya. The research stages include extracting mangrove leaves, media preparation, and testing the antibacterial inhibition zone. The results of the research showed that the antibacterial test with Escherichia coli bacteria had a weak inhibition zone of less than 10 mm with details of a 0.1 ml sample around 5.35 mm and a 0.2 ml sample around 6.78 mm at 24 hour incubation, a 0.1 ml sample measuring around 7.12 mm and the 0.2 ml sample measuring around 6.98 mm at 48 hours incubation, and for the Staphylococcus aureus bacteria there was no zone of inhibition at 24 and 48 hours incubation for both the 0.1 ml and 0.2 ml samples.